Estimation of concentration by eye contact measurement in robot-based intervention program with autistic children - Ismail, Luthffi Idzhar; Shamsudin, Syamimi; Yussof, Hanafiah; Hanapiah, Fazah Akhtar; Zahari, Nur Ismarrubie (Elsevier, 2012)

(untitled)
Lacking of eye contact in social interaction and communication is one of the impairments that being diagnosed with some of the children with Autism Spectrum Disorder (ASD). This paper presents the initial response of eye contact time between humanoid robot NAO and ASD children in Robot-based Intervention Program (RBIP) interaction and normal classroom interaction. Twelve ASD children from National Autism Society of Malaysia (NASOM) based on inclusive criteria and certain ASD characteristics are being selected to participate in this intervention program. The interaction between humanoid robot NAO and ASD children is being recorded for both RBIP interaction and normal classroom setup. The eye contact time in both interactions for each child is being observed and recorded. The eye contact of the ASD child is often seen in RBIP interaction as compared to the normal classroom interaction.